Kajian Potensi Kualitas Kayu Melalui Uji Marka Anatomi Pada Tanaman Puspa (Schima wallichii (DC.) Korth. Sebagai Tanaman Revegetasi Lahan Pascatambang - Taufiq, Ahmad; A, Alponsin (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
Revegetation is one of the way to remedy polluted area. Some plants have been applied as revegetation plant due to it has the fast-growing rate and adaptive to the critical area. Plant species which potential for revegetation has ability to live and survive and some are pioneer species. Puspa tree (Schima wallichii (D.C.) Korth.) is a pioneer species that commonly found at either primary or secondary forest and even at savana area. Puspa can be used as revegetation plant also because it is easy propagated and belonging to a semi-fire proof plant species. Therefore, ecologically, puspa suit to be used as revegetation plant species candidate for the land after mining. Besides of matching with environment, that plant should also meet with the economic use. Anatomical study had been conducted to ensure the wood use precisely based on its quality. Three samples from different locations revealed no significant differentiation by their anatomy characters. The result of observation showed the Puspa wood had a small (50-100 πm) to very small (<50 πm) pore with soliter shape and “baur” type. The Parenchyma type of Puspa wood is apotrakeal baur and medullary ray is classified to uniseriate and multiseriate, very tall and wide. This tissue comprised with two types off cell, procumbent and upright ray cell (heterocellular). The fibre had was long (> 1600 µm) with thick wall and tight lumen. The result of anatomical comparison study between Puspa’s wood with commercial wood showed Puspa belonged to hardwood group grade 1 and 2. These data should be used as a considerable report for a recommendation reference of using puspa as a plant species for the reclamation of after mining area and anyway provides economic benefit.